Maternal genetic features of the Iron Age Tagar population from Southern Siberia (1st millennium BC) - Pilipenko, Aleksandr S.; Trapezov, Rostislav O.; Cherdantsev, Stepan V.; Babenko, Vladimir N.; Nesterova, Marina S.; Pozdnyakov, Dmitri V.; Molodin, Vyacheslav I.; Polosmak, Natalia V. (PLOS ONE, 2018)
Early nomads in the Eurasian steppes since the beginning of the 1st millennium BC played a key role in the formation of the cultural and genetic landscape of populations of a significant part of Eurasia, from Eastern Europe to Eastern Central Asia. Numerous archaeological cultures associated with early nomads have been discovered throughout the Eurasian steppe belt. The Tagar archaeological culture existed in the Minusinsk basin (Sayan Mountains, Southern Siberia, Russia) in the northeastern periphery of the Eurasian steppe belt from the 8th to 1st century BC during the pre-Scythian, Scythian, and Early Xiongnu-Sarmatian periods. In this study, we evaluated mtDNA diversity in the Tagar population based on representative series (N = 79) belonging to all chronological stages of the culture. The Tagar population had a mixed mtDNA pool dominated by Western Eurasian haplogroups and subgroups (H, HV6, HV*, I, K, T, U2e, U4, U5a, and U*) and, to a lesser degree, Eastern Eurasian haplogroups (A*, A8, C*, C5, D, G2a, and F1b). The Tagar population showed a similar mtDNA pool structure to those of other Iron Age populations representing the “Scythian World.” We observed particularly high similarity between the Tagar and Classic Scythians from the North Pontic region. Our results support the assumption that genetic components introduced by Bronze Age migrants from Western Eurasia contributed to the formation of the genetic composition of Scythian period populations in Southern Siberia. Another important component of the Tagar mtDNA pool was autochthonous East Eurasian lineages, some of which (A8 and C4a2a) are potential markers of the westward genetic influence of the eastern populations of the Scythian period. Our results suggest a genetic continuity (at least partial) between the Early, Middle, and Late Tagar populations.